ANALISIS STRUKTUR MAJAS SELOKO HUKUM ADAT SEBAGAI BENTUK EKSPRESI SIMBOLIK NILAI-NILAI RELIGIUS MASYARAKAT MELAYU JAMBI - Erlina Zahar (Jurnal Ilmiah Dikdaya, 2018)
Abstract: This study aims to gain a deep understanding of: 1) The structure of the custom of Seloko adat law as a form of traditional expression of jambi Malay society, and (2) the function of majas in custom seloko text texts on Melayu Jambi society. This research is qualitative descriptive by using method hermeneutic structural analysis. The data in this study are religious values in Seloko Adat, sourced from seloko lines in a collection of custom seloko text. Primary data sources were obtained from Jambi Customary Institution documents and secondary sources derived from related researches obtained from customary stakeholder books and information or those who knew about Seloko Adat on Jambi Community. The results of this study include: 1) In general, the religious values contained in the SAMJ majoric elements, reflected the use of the type of parable of majesty, metaphoric majesty, personification of majesty, hyperbole majesty, and repetitive masters. The expressions contained in the SAMJ are symbolic or indirect, and 2) In general the religious values of the aspects of understanding the symbols in the SAMJ Jambi text are reflected in religious symbols, custom symbols, and languages. The understanding of these symbols in the text of the Jambi Malay customs center illustrates the strong belief of the Malay Jambi people against the customary relationship with the Islamic religion, so that customary symbols refer to Islam. Understanding the symbols are related to aspects of belief, appreciation, knowledge and practice of Islamic teachings in the life of the Jambi Malay community.Keywords: Figure of Speech, Seloko Adat Law, Symbolic Expression, Religious Values.